An incremental shuttle wheel test for wheelchair tennis players - de Groot, S.; Valent, L.; Fickert, R.; Pluim, B. M.; Houdijk, H. (International Journal of Sports Physiology and Performance, 2016)
Purpose: To determine the relationship between outcomes of the shuttle wheel test (SWT) and peak oxygen uptake (VO2peak) during that test and whether SWT and VO2peak can discriminate between different skill levels of wheelchair tennis players.